PENGARUH KOMPETENSI PEJABAT PENATAUSAHAAN KEUANGAN, SISTEM PENGENDALIAN INTERN PEMERINTAH PENGAWASAN KEUANGAN DAERAH TERHADAP NILAI INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada SKPD Kabupaten Kampar) - Wahyu Maheldi; Rita Anugerah; Al Azhar L ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
Assed on the result of the local government of the financial reports fiscal year 2011 to 2013 received opinions qualified opinion. The result of the examination caused by government financial statement did not complete the value of characteristics information from the financial statement it self. data collection technique used was to use questionnaer. Data analyst methods used i thisresearch is descriptive statistics data quality testing,and testing the assumsption of classical.To test this hypothesis, the user used primary data. financial administration official competence influence .026, the system of internal control influence .032 and the control of regional finance influence 0.21 After the data was analyzed, it found that all of the factor have a significally give positve influence to the value of local government financial reporting information. It means, if finance better than before, the information and financial report which produced by the government will be official competence, the system of internal control, and the control of regional finance to make financial reporting so it has information value.Keywords: Information Value, Competence, Internal Control, And Regional Finance.